The Role of Social Capital in Contributing to Lifestyle Brand-Related Content on Social Media - Anita Ciunova-Shuleska; Nikolina Palamidovska-Sterjadovska; Irena Bogoevska-Gavrilova (Economy, Business and Development: An International Journal (EB&D), 2022)
The purpose of this research is to analyze the differences in users' intentions to like, comment and share lifestyle brand-related content on social media based on the social capital focus. In this paper, social capital is conceptualized as a positive outcome of users' interaction on social media, focusing on bonding and bridging dimensions of social capital. However, in order to examine the differences in intentions to like, comment and share between social media users with bridging and bonding focus, social capital is analyzed as a cause of social media engagement in terms of liking, commenting and sharing brand-related content on social media. A survey with social media users was carried out, using questionnaires as a method of data collection. A data set of 415 effective responses is collected and factor analysis and ANOVA test was used. The respondents were divided into two groups: social media users with bridging focus and with bonding focus. The results of factor analysis identified the factors as conceptualized in the literature. The results of ANOVA test indicated existence of significant differences in intentions to like, to share and to comment lifestyle brand-related content depending on the social media users' social capital focus. Social media users with bridging focus showed stronger intentions to like, share and comment lifestyle brand-related content comparing to social media users with bonding focus. The findings of this research study may help social media marketing managers to successfully design and implement effective lifestyle brand-related content depending on the users' social capital focus.
Keywords: M31; 330; comment; lifestyle content; like; share; social capital